If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2q + -10 = q + -4 Reorder the terms: -10 + 2q = q + -4 Reorder the terms: -10 + 2q = -4 + q Solving -10 + 2q = -4 + q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1q' to each side of the equation. -10 + 2q + -1q = -4 + q + -1q Combine like terms: 2q + -1q = 1q -10 + 1q = -4 + q + -1q Combine like terms: q + -1q = 0 -10 + 1q = -4 + 0 -10 + 1q = -4 Add '10' to each side of the equation. -10 + 10 + 1q = -4 + 10 Combine like terms: -10 + 10 = 0 0 + 1q = -4 + 10 1q = -4 + 10 Combine like terms: -4 + 10 = 6 1q = 6 Divide each side by '1'. q = 6 Simplifying q = 6
| x^2-12x-57=0 | | 0=18x+10 | | y=18x+10 | | 5y-3x-4=0 | | x^2+10x+25-2x^2+2x+32=0 | | z=(x-a)/b | | 8x=-2y+8 | | -8x+15=0 | | 4a^2-4b^2+16bc-16c^2=0 | | X+3x^2=52 | | 4ln(x)=ln(81) | | 9x(-5*42)=0x | | 3y-6x+24=0 | | 9x(-5*42)=3x | | 2x[12+9]= | | -4(b-1)+2b=3(2b-1) | | 3(s+1)-(5-2)=22s | | 7k+7k=-5(8k-6)-6(k+5) | | 5-3x+5x=-8+g+9x | | 16z-32+9=22+86 | | 16z-32+9=22-86 | | -45v+9v^2-63v^3=0 | | .01x^2-.1x-.3=0 | | -8n^5+5n^3+6n=0 | | (8n+5)(4n^2-4n-2)=0 | | 0.25*1/4^2x=1 | | x^6+i=0 | | -1/3x-2/9=-1 | | (4p+4)(2p+7)=0 | | 108x^4-46x^2-8=0 | | x^2+px+12=0 | | (3x+4x^2-6x^4)-(7x^3-3x^2+5x)=0 |